DIELECTRIC RELAXATION STUDY OF MIXTURES OF METHANOL AND DIMETHYLAMINOETHANOL USING TIME DOMAIN REFLECTOMETRY - V. L. JADHAVPATIL; P. B. UNDRE; S. N. HELAMBE (International Journal of Pharma and Bio Sciences, 2013)
Dielectric relaxation measurements on Methanol – Dimethylaminoethanol solvent mixtures have been carried out across the entire concentration range using Time Domain Reflectometry technique at 15, 25, 35 and 450C over the frequency range from 10 MHz to 20 GHz. The mixtures exhibit a principle dispersion of the Davidson-Cole relaxation type at microwave frequencies. The Bilinear calibration method is used to obtain complex permittivity e*(w) from complex reflection coefficient r*(w) over the frequency range 10 MHz to 10 GHz. The excess permittivity (eE), excess inverse relaxation time (1/t)E, Kirkwood correlation factor (geff) and thermodynamic parameters are also calculated to study the Solute-Solvent interaction.